Propugnating Effect of Bark of Rhizophora mucronata Against Different Toxicants Viz Carbon Tetrachloride, Ethanol and Paracetamol on HepG2 Cell Lines - Chitra Jairaman; Syed Ali Mohamed Yacoob; Anuradha Venkatraman; Yogananth Nagarajan; Gnanadesigan Murugesan (Korean Pharmacopuncture Institute, 2019)
Objective: The aim of the study was to evaluate the hepatoprotective activity of the bark extract (Ethanol: Water) in the ratio of (3:1) of Rhizophora mucronata (BERM) by intoxicating the HepG2 cell lines with different toxicants viz, CCL4, Ethanol and Paracetamol with different concentrations of the extract were used. The HepG2 cell lines were subjected to MTT Assay for studying the cytotoxicity. Methods: HepG2 cells were plated using 96 well plate in 10% bovine serum, exposed to different toxicants viz, 2% CCl4, 60% Ethanol and 14 mM Paracetamol respectively. The various test concentrations (18.85, 37.5, 75, 150 and 300 μg/ml) of bark extract of Rhizophora mucronata was added and incubated for 24 hours. Medium was removed after incubation period and 0.5 mg/ml MTT(3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) was added and again incubated for 4 hours at 37oC. Then MTT was removed the crystals was dissolved in DMSO and absorbance was measured at 570 nm. Results: The result showed that dose dependent increase in percentage of viability at the doses of 18.85, 37.5, 75, 150, 300 μg/ml. The results for the CCl4 intoxicated, at 300 μg/ml of the concentration of the extract, the % of viable cells was found out to be 99.6%, for Ethanol intoxicated, 97.67%, and Paracetamol induced, 75.37%, IC50 was 21.53 μg/ml, 12.61 μg/ml and 21.42 μg/ml respectively. Conclusion: Thus, we conclude that, the extract possesses defensive effect against different toxicants and can be used as an alternate drug for hepatotoxicity.